Simulasi Banjir Sungai Putri Danau Sipin Kota Jambi - Tri Wahyu Noer Hidayath; Azwarman Azwarman; Ria Zulfiati (Jurnal Talenta Sipil, 2023)
River is one of the water resources that is widely used to meet raw water needs. Along with changing conditions in the river basin, changes in land use and population growth make the river not function optimally as it should. One of the natural phenomena that threatens the existence of human life in several regions in Indonesia every time the rainy season enters it is sure to experience flooding, especially in the Jambi city area. This is due to the reduced capacity of the drainage cross-section so that with high rainfall it is no longer able to accommodate flood discharges resulting in overflow of water. The purpose of this study is to determine the difference between the Sungai Putri flood discharge and Q25 and identify flood points and provide solutions to flood problems that occur in the river / or in the Sungai Putri Lake Sipin drainage, Jambi city. In this study, secondary data used for 10 years of rainfall and cross-sectional data of Putri River drainage. The results of the calculation of the planned flood discharge using the rational mononobe method Q2 = 18,695 m3/s, Q5 = 23,171 m3/s, Q10 = 26,397 m3/s, Q20 = 30,021 m3/s and Q25 = 30,804 m3/s. And the next step using the HAC-RAS 3.13 software. After being analyzed using software, the drainage point that cannot accommodate the incoming flow, it is necessary to redesign the Putri River so that it can accommodate the water capacity that occurs every year due to high rainfall.